THE USE OF INTERMEDIATE HYDROPHOBIC SILICA NANOPARTICLES FOR STABILIZATION OF WATER-IN-CO2 EMULSION AT TEMPERATURE 120 OC AND VARIOUS WATER SALINITIES - Wicaksono
Surfactant-stabilized CO2 foam is usually not stable at very high temperature. Applications of nanotechnology have been developing fast in many disciplines. Petroleum industry quickly responds to such a technology and the efforts are being focused to the research areas such as EOR nanoparticle- CO2 foam. Types of the foam generated depend on wettability of the nanomaterial employed and the wettability may influence stability of the CO2 foam at certain conditions, particularly at high salinity and very high temperature. High salinity may cause the nanoparticle to coagulate and very high temperature can result in instability of the nanoparticles due to higher mobility and agitation. These all cause the foam to become unstable. The previous works on such areas rarely consider extreme reservoir conditions such as high salinity and very high temperature. The common temperature used is not more than 95 oC. Therefore, the present research is directed to investigating the performance of intermediate wet silica nanoparticles that is expected to have high resistance at various values of water salinity and very high temperature as the stabilizing agent. The salinity and temperature used in this work is as high as 6.5% and 120 oC, respectively. Herein, both the nanosilica concentration and salinity are varied. In the first stage of experiments, tube tests are conducted to ensure capability of the nanosilica to form stable emulsion. Iso-octane is employed to replace supercritical CO2 at atmospheric conditions and therefore we use iso-octane during tube tests. It was obtained that ethanol and ethylene glycol at certain ratio are needed to disperse the nanoparticles in brine and the water-in-iso-octane emulsion was stable. For a given nanosilica concentration, it was found that the emulsion volume formed was slightly affected by water salinity. Generation of CO2 foam at high pressure and high temperature is performed by injecting the nanoparticle suspension and supercritical CO2 alternately into 30- inch Berea sandstone which serves as the foam generator. The foams are than collected in the sight glass at pressure and temperature of 1500 psi and 120 oC, respectively. The CO2 foam column in the sight glass was then observed and recorded for 24 hours. Results obtained demostrate that stable CO2 foam at 120 oC can be generated for at least 24 hours by employing intermediate wet silica nanoparticles. The stability of CO2 foam is not affected by either salinity of 10000 - 65000 ppm NaCl or nanosilica concentration used 5000 - 12500 ppm. This indicates that the high adsorption energy of the silica stimulates the formation of solid lamella at the CO2- water interface to protect the emulsion/foam from breaking. This research demostrates that such a silica has its potential as emulsion/foam stabilizer to be used in the application of CO2 flooding. Promoting CO2 as an EOR fluid offers contribution to carbon capture and sequestration program in reducing green house effect.